2014
DOI: 10.3390/en7031149
|View full text |Cite
|
Sign up to set email alerts
|

An Artificial Neural Network Compensated Output Feedback Power-Level Control for Modular High Temperature Gas-Cooled Reactors

Abstract: Small modular reactors (SMRs) could be beneficial in providing electricity power safely and also be viable for applications such as seawater desalination and heat production. Due to its inherent safety features, the modular high temperature gas-cooled reactor (MHTGR) has been seen as one of the best candidates for building SMR-based nuclear power plants. Since the MHTGR dynamics display high nonlinearity and parameter uncertainty, it is necessary to develop a nonlinear adaptive power-level control law which is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…In recent decades, nuclear reactor technology has continued to be developed and mature. The breakthrough in large-scale desalination technology has made it possible to develop commercial-scale desalination production, and it has been proven technically feasible to replace conventional energy with nuclear energy for desalination [15][16][17]. At the beginning of this century, Tsinghua University employed the seawater desalination economic evaluation program (DEEP 2.0 software) developed by IAEA to evaluate the economic performance of the HTGR coupled reverse osmosis method (HTGR-RO), which could produce fresh water 480,000 m 3 /d, and the results showed that it was more economical than fossil fuels [18].…”
Section: Introductionmentioning
confidence: 99%
“…In recent decades, nuclear reactor technology has continued to be developed and mature. The breakthrough in large-scale desalination technology has made it possible to develop commercial-scale desalination production, and it has been proven technically feasible to replace conventional energy with nuclear energy for desalination [15][16][17]. At the beginning of this century, Tsinghua University employed the seawater desalination economic evaluation program (DEEP 2.0 software) developed by IAEA to evaluate the economic performance of the HTGR coupled reverse osmosis method (HTGR-RO), which could produce fresh water 480,000 m 3 /d, and the results showed that it was more economical than fossil fuels [18].…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the nuclear societies worldwide have been developing new and innovative reactors with the objective of guaranteeing safety under any circumstances and in natural disasters. Due to the increment of the requirements for the nuclear safety and security [1], there are a lot of research and technology developments to improve the safety, sustainability, efficiency, and cost in nuclear power plants (e.g., Generation IV reactors [2,3], Thorium reactors [4], and small modular reactors [5,6]). Currently, the research on small modular reactors (SMRs) is increasing rapidly owing to the advantages of these devices.…”
Section: Introductionmentioning
confidence: 99%
“…To guarantee the stability of the closed-loop formed by subsystem (34) and (18), it is necessary to design a proper online adaptation law of ˆi  (i = 1, 2). Thus, define the expanded Lyapunov function as…”
Section: Remarkmentioning
confidence: 99%
“…By adopting point kinetics with one equivalent delayed neutron group, by considering the temperature feedback effect of the reactor core composed of both the pebble-bed and reflector, and based upon the conservation law of thermal energy, the dynamic model for control design can be written as [15,18]:…”
Section: Nonlinear State-space Model For Control Designmentioning
confidence: 99%
See 1 more Smart Citation